BIBLIOMETRIC ANALYSIS OF MSME PERFORMANCE: TRENDS, VARIABLE RELATIONSHIPS, AND RESEARCH GAPS - Nandiroh, Umi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to analyze the factors influencing the performance of Small and Medium Enterprises (SMEs) through a bibliometric approach, exploring the relationships between variables such as financial literacy , access to finance , business innovation, and risk management . The research methodology involves bibliometric analysis using VOSviewer to map research trends and the relationships between variables affecting SME performance. Data analyzed were sourced from articles published in the Scopus database between 2000 and 2024, using the keywords “SMEs Performance” and “SMEs Financial Performance” . The findings reveal that financial literacy and access to finance significantly impact the financial performance of SMEs, while product and business model innovation play a crucial role in enhancing competitiveness and sustainability. Additionally, effective risk management enhances the resilience of SMEs in times of crisis. The research trends indicate a shift in focus from financial performance to non-financial dimensions such as sustainability and social innovation . Future research is recommended to explore social innovation , risk management in the context of pandemics , and the interplay between social and financial capital in SMEs through longitudinal studies to better understand their long-term impact on SME performance.